1987
DOI: 10.21236/ada204175
|View full text |Cite
|
Sign up to set email alerts
|

Signal Detection in Arctic Under-Ice Noise

Abstract: S k C I This paper treats a signal detection problem using arctic under-ice noise. The authors have had access to one large segment of data (6150144 samples), which is nonstationary and has been shown to be non-Gaussian. A model is presented for the arctic under-ice noise, and the performance levels achieved by several different detectors are compared. The association between the shape of the empirical probability density function and the shape of the power spectrum is explored. The arctic noise is known to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…GG distributions can also model noise distributions that appear in non-standard wireless media. In Nielsen and B.Thomas (1987) the authors showed that Arctic under-ice noise is well modeled by members of the GG family. In Banerjee and Agrawal (2013) the GG family has been recognized as a model for the underwater acoustic channel where values of p = 2.2 and p = 1.6 have been found to model the ship transit noise and the sea surface agitation noise, respectively.…”
Section: Past Workmentioning
confidence: 99%
“…GG distributions can also model noise distributions that appear in non-standard wireless media. In Nielsen and B.Thomas (1987) the authors showed that Arctic under-ice noise is well modeled by members of the GG family. In Banerjee and Agrawal (2013) the GG family has been recognized as a model for the underwater acoustic channel where values of p = 2.2 and p = 1.6 have been found to model the ship transit noise and the sea surface agitation noise, respectively.…”
Section: Past Workmentioning
confidence: 99%
“…It has also been discussed that the GGD better approximates impulsive atmospheric noises in several communication scenarios [85], [86]. Moreover, additive noise that arises in non-standard wireless media, such as under-ice noise and sea-surface agitation noise in underwater acoustics can also be modeled using GGD [87], [88]. Therefore, GGD exhibits a more appropriate fit to the noise data collected over a varied range of physical channel conditions [89], [90].…”
Section: B Related Work and Motivationmentioning
confidence: 99%